Environmental life cycle feasibility assessment of hydrogen asan automotive fuel in Western Australia - Biswas, Wahidul; Thompson, Brett; Islam, Mohammad Nazrul (Elsevier Ltd, 2012)
A life cycle assessment has been undertaken in order to determine the environmental feasibility of hydrogen as an automotive fuel in Western Australia. The criterion for environmental feasibility has been defined as having life cycle impacts equal to or lower than those of petrol. Two hydrogen production methods have been analysed. The first is steam methane reforming (SMR), which uses natural gas (methane) as a feedstock. The second method analysed is alkaline electrolysis (AE), a mature technology that uses water as a feedstock. The life cycle emissions and impacts were assessed per kilometre of vehicle travel. Initial results found that hydrogen production under the SMR scenario produced less greenhouse gas, photochemical oxidation and eutrophication emissions per kilometre than petrol. Petrol produced less greenhouse gas and eutrophication emissions than hydrogen produced under the AE scenario, but the only improvement was in the terms of photochemical oxidation missions. “Hotspot” analysis showed that while the usage life cycle phase of hydrogen produced very few emissions, the reliance on electricity and fossil fuels during production was responsible for emission levels higher than those from petrol. After wind-generated electricity was incorporated, the emissions were significantly reduced below the levels of those from petrol under both SMR and AE scenarios. However, with the incorporation of wind-generated electricity, the production of hydrogen, particularly from electrolysis, is more environmentally friendly than the SMR process.